Lesions of The Eyeball and Ocular Adnexa - Our Experience Over A Period of 18 Months - Vartak, Shailesh; Neelakantan, Amrita; Chakravarty-Vartak, Urmi (Annals of Pathology and Laboratory Medicine, 2019)
BACKGROUND: The eyeball is a unique sensory organ, with a varied spectrum of lesions, which are rare with subtle presentation, thus posing diagnostic challenges. Our aim is to evaluate histomorphology of lesions of eye and ocular adnexa, classify and compare with other studies. METHODS: All biopsies and specimens of eyelid, eyeball and orbital lesions received in histopathology section of our Pathology department between January 2017 and June 2018 were analysed and a total 43 cases were evaluated. RESULTS: The age distribution of cases analysed ranged from 6 years to 85 years with mean age of 39 years and equal gender distribution. Neoplastic lesions (53.49%) were more common than non-neoplastic lesions. Among neoplastic lesions, benign (56.52%) were more common than malignant. The most common non-neoplastic lesion was zygomycosis of orbit (75%), epidermal cyst in eyelid (30%) and granulation tissue in eyeball (50%).The only benign tumour in orbit was meningioma. The most common benign tumour in eyelid was hemangioma (50%) and in eyeball, we encountered 1 pigmented nevus of conjunctiva and 1 apocrine hidrocystoma. Common malignant eyelid tumours were basal cell carcinoma and sebaceous carcinoma(33.33% each) , whereas in orbit we received 1 basal cell carcinoma and 1 adenoid cystic carcinoma. In eyeball, we encountered 1 basal cell carcinoma and 1 squamous cell carcinoma of conjunctiva. CONCLUSION: Most of the studies done in this arena focus on either adnexa or orbit alone, and through our study we have tried to understand the frequency of occurrence and histomorphology of all lesions pertaining to eyeball, orbit and adnexa .